PELATIHAN KEMAMPUAN KOMUNIKASI OLEH MAHASISWA IBM BEKASI DI MASA PANDEMI DALAM PERSPEKTIF TEORI ACTION ASSEMBLY (Studi Fenomenologi Pada Karang Taruna - RENI NOVIA (Institut Bisnis Muhammadiyah Bekasi, 2021)
This research has a problem formulation about, How is the communication skillstraining by IBM Bekasi students in the Covid 19 period, in the perspective of theAction Assembly theory (Phenomenology Study on Youth Organization). In theperspective of assembly action theory. This research uses a qualitative approach.Likewise, the research methods are both qualitative in nature. Data collection isobtained through observation and in-depth interviews with key informants, whileinformant data is obtained through literature study from sources such as photodocumentation, printed media, journals, and others. The results of the study, infactual conditions, phenomenology regarding training designed by IBM Bekasistudents has been processing assertion messages, by (1) students describing theexisting conditions as they are, (2) expressing the intent and purpose of workingtogether with youth organizations to empower youth with communication skillstraining. (3) expressed a desire for an appropriate and beneficial training time forKarang Taruna, IBM Bekasi Students, and the local community.